Optimization of the Performance of the Intelkam Sat Kamneg Unit Through Early Detection Activities to Reduce the Occurrence of Mobile Cases in the Jurisdiction of the Lamongan Police - Putri, Komang Wiwin Tribuana (Advances in Police Science Research Journal, 2024)
The focus of this thesis research was motivated by the phenomenon of high cases of criminal acts of mobbing in Lamongan, especially in this case the raid carried out by silat universities. Therefore, a study was conducted to describe the implementation of early detection and explain Satintelkam's cooperation in reducing mobbing in Lamongan. To overcome this, Lamongan Police through the function of the Security Intelligence Unit with Early Detection activities seeks to perform tasks for cases of mobbing in the jurisdiction of Lamongan Police Station. The theories and concepts used by the author in answering problems are Management theory, cooperation theory, optimization concepts, and analyzing using police operational guidelines based on Perkabik No. 1 of 2023 and HTCK Satintelkam Lamongan Police.This research was conducted with a qualitative approach and used the type of field research. The findings of this study, namely in the implementation of Early Detection, and Cooperation carried out by Satintelkam obtained results found in that the implementation has not been carried out masimally by finding the implementation of administrative preparation, use of sarpras and reporting that has not been optimal. In the cooperation carried out by Satintelkam with other functions has not been optimal with the findings below the lack of communication with Satreskrim and not coordinating on target targets that have the potential for interference to be prevented with Satbinmas Based on the results of the study, the conclusion found that the implementation of detection has not been optimal in reducing cases of criminal acts of mobbing, there is still a shortage in terms of organizational resources that hinder early detection activities, so the author suggests a proposal to improve the quality and quantity of members and the use of technology to optimize early detection activities.